Direct-Acting Oral Anticoagulants: Practical Considerations for Emergency Medicine Physicians - W. Frank Peacock; Zubaid Rafique; Adam J. Singer (Emergency Medicine International)
Nonvalvular atrial fibrillation- (NVAF-) related stroke and venous thromboembolism (VTE) are cardiovascular diseases associated with significant morbidity and economic burden. The historical standard treatment of VTE has been the administration of parenteral heparinoid until oral warfarin therapy attains a therapeutic international normalized ratio. Warfarin has been the most common medication for stroke prevention in NVAF. Warfarin use is complicated by a narrow therapeutic window, unpredictable dose response, numerous food and drug interactions, and requirements for frequent monitoring. To overcome these disadvantages, direct-acting oral anticoagulants (DOACs)—dabigatran, rivaroxaban, apixaban, and edoxaban—have been developed for the prevention of stroke or systemic embolic events (SEE) in patients with NVAF and for the treatment of VTE. Advantages of DOACs include predictable pharmacokinetics, few drug-drug interactions, and low monitoring requirements. In clinical studies, DOACs are noninferior to warfarin for the prevention of NVAF-related stroke and the treatment and prevention of VTE as well as postoperative knee and hip surgery VTE prophylaxis, with decreased bleeding risks. This review addresses the practical considerations for the emergency physician in DOAC use, including dosing recommendations, laboratory monitoring, anticoagulation reversal, and cost-effectiveness. The challenges of DOACs, such as the lack of specific laboratory measurements and antidotes, are also discussed.